INNOVATION TECHNOLOGIES IN ROAD CONSTRUCTION MATERIAL SCIENCE - Ya. N. Kovalev (Наука и техника, 2015)
Activation technologies of road construction materials considered in a single package represent an up-to-date progressively developing scientific and research direction in the transport material science. The essence of the activation technology for materials lies in an intensive increase of physical and chemical activity of their components in the interphase boundaries that is realized in various technological conversions. It has been established that being chemically passive under normal conditions all the materials, irrespective of their nature and aggregate state, can be chemically active under specific conditions. Such approach makes it possible to use low-active cheap silica raw material and technogenic production wastes for creation of strong composite materials on their basis.Development of the activation technologies for solidand liquid –phase components of road construction composite materials is gradually transformed in a special branch of material science that is coprology. The branch is presupposed to develop a theory and solve applied problems directed on efficient usage of technogenic production wastes as cheap raw material source for obtaining a wide range of construction materials for general and special application. Further investigation is to execute a technical modernization and develop technological equipment for activation of solid, liquid and gaseous components of road construction composite materials. In this respect all technological solutions should serve for general purpose that is to ensure optimum structures of the obtained materials that provides their longevity with minimum resource expenses and maximum level of environmental protection.